8th International conference on management and rehabilitation of chronic respiratory failure: the long summaries – part 2. Issue 1 (December 2015) - Ambrosino, Nicolino; Casaburi, Richard; Chetta, Alfredo; Clini, Enrico; Donner, Claudio; Dreher, Michael; Goldstein, Roger; Jubran, Amal; Nici, Linda; Owen, Caroline; Rochester, Carolyn; Tobin, Martin; et al.
Abstract This paper summarizes the Part 2 of the proceedings of the 8th International Conference on Management and Rehabilitation of Chronic Respiratory Failure, held in Pescara, Italy, on 7 and 8 May, 2015. It summarizes the contributions from numerous experts in the field of chronic respiratory disease and chronic respiratory failure. The outline follows the temporal sequence of presentations. This paper (Part 2) includes sections regarding: Promoting Physical Activity across the Spectrum of COPD (Physical activity: definitions, measurements, and significance; Increasing Physical Activity through Pharmacotherapy in COPD); Pulmonary Rehabilitation in Critical Illness (Complex COPD with comorbidities and its impact during acute exacerbation; Collaborative Self-Management in COPD: A Double-Edged Sword?; and Pulmonary Rehabilitation in Critical Illness.